The Effectiveness of Weed as Beetle Bank Against Abundance of Soil Arthropods on Corn (Zea mays. L) - Sa'adah, Anis; Haryadi, Nanang Tri (Graduate School, Universitas Brawijaya, 2021)
Conservation of natural enemies on maize can be done by utilizing grass weeds as Beetle banks. Natural enemies of shelter and get food from the weed grasses that are in the land irrigated corn. Natural enemies observed in this research were the predator of ground arthropods in the form of ground beetles, tomcat, and predators arthropods in other lands. The trap used is the Pitfall trap. The percentage of arthropod predators was 69%, and arthropods herbivore was 31%. The abundance of soil arthropods in the treatment of weeds grass is higher than the control treatment It is because of the treatment of weed grass soil arthropods get habitat for a place to stay. Weed grasses provide food sources for the arthropods and get protection from an environment that is less supportive. The use of weed grasses in addition to Beetle banks also serves as a place to breed. The highest abundance of arthropods was situated on the treatment Eleusine indica that has a lush lawn and has a characteristic odor favored by arthropods. Arthropods that acts as a predator in the land are the family of Formicidae, Philodromidae, Carabidae, Staphylinidae, Pentatomidae. Some Arthropods from the Pentomidae family have a role as a pest and others as natural predators or predators. Arthropods found in the research was an arthropod that had a role as natural enemies or predator. The Pentomidae family that has a position as a predator is Picromerus Bidens. Ground beetles were found in the C. fossor and Pheropsophus sp. Ground beetles are dominant picking weeds Setaria sp. and Eleusine indica as habitat and place in search of food and life's survival. Keywords: Beetle bank, soil arthropods, weeds.